Screening the Suitability of Levee Protected Areas for Strategic Floodplain Reconnection Along the LaGrange Segment of the Illinois River, USA. (8th July 2016) - Remo, J. W. F.; Guida, R. J.; Secchi, S.
Abstract: Levee‐protected floodplains along the 125‐km LaGrange Segment (LGS) of the Illinois River were screened for their abiotic suitability for alternative ecosystem services (ESs), including wetland creation, habitat, floodwater denitrification and flood‐tolerant agriculture. The suitability framework developed for this study builds upon the Land Capability Potential Index and is informed by the current understanding of the linkages between river hydrology, hydraulics, floodplain soils, floodplain vegetation and floodplain nutrient cycling. In addition to screening these floodplain areas for alternative ESs, we demonstrate how this framework can be combined with economic assessments of current floodplain services to inform how strategic floodplain reconnection (i.e. restoration of hydrologic linkages between river and floodplain for the purpose of flood mitigation and provisioning of alternative ESs) could be used to work towards sustainable floodplain management. Results show that ESs increase with upstream distance from the LaGrange Lock and Dam. This is attributed to the operation of the lock and dam generating a water level that would result in the inundation of a substantial portion of floodplain (>70 km 2 ) up to ˜60 km upstream if the levees were to be removed or set back. Comparison of the profits from current floodplain agriculture with the potential profits of flood‐tolerant agriculture suggests that overcoming the economic costs of floodplain reconnection within the LGS will likely require both conversion of reconnected floodplain lands to flood‐tolerant agriculture and payments for ESs. Copyright © 2016 John Wiley & Sons, Ltd.